Nominal Wage Flexibility, Wage Indexation and Monetary Union - Lars Calmfors; Åsa Johansson (Center for Economic Studies and ifo Institute (CESifo), 2002)
Membership in a monetary union implies stronger incentives for nominal wage flexibility in the form of wage indexation and shorter contract length than nonmembership. For example, entry into a monetary union may cause a move from a non-indexation to an indexation equilibrium. But more wage flexibility is only an imperfect substitute for an own monetary policy. It is possible that an increase in wage flexibility is welfare-decreasing because of the accompanying rise in price variability. The interaction between wage setting and central bank behaviour may result in either multiple equilibria or a unique full-indexation equilibrium.
Keywords: 330; nominal wage flexibility; wage indexation; monetary union; asymmetric shocks